Forest Biosecurity Systems and Processes: An Indian Perspective - Gupta, Kavita; Sankaran, K. V. (Frontiers in Forests and Global Change, 2021)
This paper reviews the legislation for plant biosecurity applicable to the agriculture and forestry sectors in India and suggests how it can be strengthened to achieve the desired goals. We also highlight the risks associated with the small and bulk imports of plants/ plant materials to India and present the types of pests/pathogens commonly intercepted at the border. Our suggestions to improve plant biosecurity in India include 1) revising and updating the current legislations viz., the Destructive Insects & Pests Act (1914) and Plant Quarantine Order 2003, 2) improving biosecurity infrastructure by establishing more plant quarantine stations with state-of-the art facilities, 3) establishing a National Sanitary and Phytosanitary Database Center for easy exchange of information and 4) establishing a Biosecurity and Trade Unit with independent cells with key responsibilities for scrupulous implementation of regulations. The information and research gaps in various fields are also identified. The paper proposes that the emerging pest threats in India can be managed through an integrated pest management system, by using e-pest surveillance, establishment of pest-free areas and promotion of biocontrol of pests and pathogens where applicable. A new legislation, viz., the Pesticides Management Bill introduced by the Indian Parliament in 2020 is expected to provide a framework to address all issues concerning production and use of pesticides in the country. We recognize that the use of new technologies for remote sensing, detection and mapping of vegetation can greatly advance bio-surveillance, forecasting, and monitoring of pests and associated management activities. To realize the plant biosecurity goals, India may also strengthen regional cooperation to: 1) harmonize regulations for sanitary/phytosanitary and plant quarantine/biosafety measures and 2) use a common pest risk analysis in the region. An inclusive effort among different sectors working on plant biosecurity through adoption of an overarching cross-sectoral legislation will minimize pest escapes. Capacity-building of officials to identify risky goods and verify conformity with Import Health Standards is raised. Involvement of all stakeholders in implementing the legislation and raising biosecurity awareness among all concerned are also mandatory. An Agriculture Biosecurity Bill currently considered by the Govt of India is expected to address the inadequacies.